2009
DOI: 10.1186/1742-4690-6-s3-p266
|View full text |Cite
|
Sign up to set email alerts
|

P16-37. HIV controllers with weak CD8+ T cell responses maintain a tight control of infection despite carrying infectious viruses

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Evidence in macaques have shown that SIV viral load and proviral DNA were rapidly increased after CD8 depletion in vivo (112,113) and decreased when CD8 + cells returning back (9). Studies in ex vivo and in vitro also present an ability of CD8 + T cells to suppress viral replication as seen in animal model (114)(115)(116). HIV Gag-specific CD8 + T cell response is associated with low plasma viral load (117)(118)(119)(120).…”
Section: Adaptive Immunitymentioning
confidence: 98%
See 1 more Smart Citation
“…Evidence in macaques have shown that SIV viral load and proviral DNA were rapidly increased after CD8 depletion in vivo (112,113) and decreased when CD8 + cells returning back (9). Studies in ex vivo and in vitro also present an ability of CD8 + T cells to suppress viral replication as seen in animal model (114)(115)(116). HIV Gag-specific CD8 + T cell response is associated with low plasma viral load (117)(118)(119)(120).…”
Section: Adaptive Immunitymentioning
confidence: 98%
“…Studies in ex vivo and in vitro also present an ability of CD8 + T cells to suppress viral replication as seen in animal model (114)(115)(116). HIV Gag-specific CD8 + T cell response is associated with low plasma viral load (117)(118)(119)(120). Polyfunctionality such as MIP-1β, IFNγ, TNFα, CD107a as degranulation marker and IL-2 (11,121) and effective proliferative capacity (122) have been remarked in HIV controllers.…”
Section: Adaptive Immunitymentioning
confidence: 99%